Effects of Omeprazole and Aluminum Hydroxide/Magnesium Hydroxide on Riociguat Absorption. (1st March 2016) - Becker, Corina; Frey, Reiner; Unger, Sigrun; Artmeier‐Brandt, Ulrike; Weimann, Gerrit; Mück, Wolfgang
Abstract : Riociguat, a soluble guanylate cyclase stimulator, is a novel therapy for the treatment of pulmonary hypertension. Riociguat bioavailability is reduced in neutral versus acidic conditions and therefore may be affected by concomitant use of medications that increase gastric pH. The effect of coadministration of the proton pump inhibitor omeprazole or the antacid AlOH/MgOH on the pharmacokinetics, safety, and tolerability of riociguat 2.5 mg was characterized in two open‐label, randomized, crossover studies in healthy males. In study 1, subjects pretreated for 4 days with omeprazole 40 mg received cotreatment with omeprazole plus riociguat or riociguat alone (no pretreatment) on day 5 ( n = 12). In study 2, subjects received cotreatment with 10 mL AlOH/MgOH plus riociguat or riociguat alone ( n = 12). Pre‐ and cotreatment with omeprazole decreased riociguat bioavailability (mean decreases in area under the plasma concentration‐time curve [AUC] and maximum concentration in plasma [ C max ] were 26% and 35%, respectively). Cotreatment with AlOH/MgOH resulted in greater decreases in riociguat bioavailability (mean decreases in AUC and C max were 34% and 56%, respectively). In both studies, most adverse events (AEs) were of mild intensity, and no serious AEs were reported. No additional safety signals were identified. Treatment with riociguat, with or without omeprazole or AlOH/MgOH, was well tolerated, with a good safety profile. Owing to the resulting increase of gastric pH, riociguat bioavailability is reduced by coadministration with AlOH/MgOH and, to a lesser extent, by coadministration with omeprazole. Thus, antacids should not be administered within an hour of receiving riociguat, but no dose adjustment is required for coadministration of proton pump inhibitors.